FROM EXPOSITION TO RESOLUTION: CHARACTER DYNAMICS AND PLOT IN "THE CHILDE 2023" - Yulianto, Andrias; Simamora , Ucok Panda (Prologue: Journal on Language and Literature, 2025)
Exploring plot and techniques such as dialogue presentation and implicit character traits provides a deeper understanding of how these elements contribute to the narrative structure. Through a qualitative descriptive method, this paper examines the progression of the plot from exposition to resolution, shedding light on the interconnectedness of characterization and plot development in cinematic storytelling. The renowned film "The Childe 2023" showcases dynamic characterizations throughout the storyline. This analysis explores the intricate interplay between character evolution and the narrative techniques employed in movies to develop each character's persona and to shape and reinforce the plot. There are at least 17 distinct personality traits depicted and techniques for portraying these personalities including explicit presentation through dialogue and implicit portrayal through actions and interactions. Along with that, personality depiction techniques have been identified, such as presenting explicit dialogue from others and implicitly showing how characters speak, dress, act, and think. By examining these elements of characterization thoroughly, the researcher could also determine the main structure of the film, including the exposition, rising action, climax, falling action, and resolution. The interconnectedness of characterization elements and plot development was evident, as character arcs intertwined with the narrative trajectory, shaping the film's overarching storyline.